Ancestral protein resurrection and engineering opportunities of the mamba aminergic toxins - Guillaume Blanchet (Nature Portfolio, 2017)
Abstract Mamba venoms contain a multiplicity of three-finger fold aminergic toxins known to interact with various α-adrenergic, muscarinic and dopaminergic receptors with different pharmacological profiles. In order to generate novel functions on this structural scaffold and to avoid the daunting task of producing and screening an overwhelming number of variants generated by a classical protein engineering strategy, we accepted the challenge of resurrecting ancestral proteins, likely to have possessed functional properties. This innovative approach that exploits molecular evolution models to efficiently guide protein engineering, has allowed us to generate a small library of six ancestral toxin (AncTx) variants and associate their pharmacological profiles to key functional substitutions. Among these variants, we identified AncTx1 as the most α1A-adrenoceptor selective peptide known to date and AncTx5 as the most potent inhibitor of the three α2 adrenoceptor subtypes. Three positions in the ρ-Da1a evolutionary pathway, positions 28, 38 and 43 have been identified as key modulators of the affinities for the α1 and α2C adrenoceptor subtypes. Here, we present a first attempt at rational engineering of the aminergic toxins, revealing an epistasis phenomenon.